Inorganic and bioinorganic molecular mechanics modeling: the problem of the force field parameterization - Comba, Peter; Remenyi, Rainer (Coordination chemistry reviews, 2003)
A short account of the fundamental principles of molecular mechanics modeling of inorganic compounds, based on recent review articles, is followed by a review of methods for the tuning and validation of force fields. As a case study we then concentrate on recent developments in the modeling of blue copper proteins. Advantages and limitations of purely quantum mechanical methods, QM/MM approaches and empirical force field calculations, as well as the problem of the validation of the results are discussed in detail.